2021
DOI: 10.1186/s13099-021-00443-3
|View full text |Cite
|
Sign up to set email alerts
|

In silico molecular docking and in vitro antimicrobial efficacy of phytochemicals against multi-drug-resistant enteroaggregative Escherichia coli and non-typhoidal Salmonella spp.

Abstract: Background In the wake of emergence of antimicrobial resistance, bioactive phytochemical compounds are proving to be important therapeutic agents. The present study envisaged in silico molecular docking as well as in vitro antimicrobial efficacy screening of identified phytochemical ligands to the dispersin (aap) and outer membrane osmoporin (OmpC) domains of enteroaggregative Escherichia coli (EAEC) and non-typhoidal Salmonella spp. (NTS), respectively. Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…The next stage is to investigate the antimicrobial activities of the chosen compound in vitro and in vivo based on the good binding score in the docking study of the drugs to the selected target protein . Several target proteins in the bacterial system, such as biofilm-forming proteins, virulence proteins, the efflux pump, biofilm regulating transcriptional factors, and virulence proteins, can be chosen as a target protein for a molecular docking study to screen potential antibiofilm, antibacterial, and antivirulence phloroglucinol derivatives. Using in silico and in vitro studies, author Abdelmalek et al isolated and identified some of the potential phloroglucinol derivatives that demonstrate antibacterial and antifungal activity from the Callistemon citrinus .…”
Section: Alternative Strategies Employed For the Application Of Pg An...mentioning
confidence: 99%
“…The next stage is to investigate the antimicrobial activities of the chosen compound in vitro and in vivo based on the good binding score in the docking study of the drugs to the selected target protein . Several target proteins in the bacterial system, such as biofilm-forming proteins, virulence proteins, the efflux pump, biofilm regulating transcriptional factors, and virulence proteins, can be chosen as a target protein for a molecular docking study to screen potential antibiofilm, antibacterial, and antivirulence phloroglucinol derivatives. Using in silico and in vitro studies, author Abdelmalek et al isolated and identified some of the potential phloroglucinol derivatives that demonstrate antibacterial and antifungal activity from the Callistemon citrinus .…”
Section: Alternative Strategies Employed For the Application Of Pg An...mentioning
confidence: 99%
“…based tool that provides important information about druglikeness and pharmacokinetic properties of bioactive molecules [42,43]. In this perspective, the theoretical agreement of synthesized compounds to Lipinski's rule of five and Veber's rule [30,31,44], as well as the pharmacokinetic and toxicity parameters, was estimated using ADMET descriptors by a SwissADME [31] and PreADMET [45] online servers.…”
Section: In Silico Admet Prediction Swissadme Is a Web-mentioning
confidence: 99%
“…As a result, bioequivalent oral medication formulations are more likely to be produced by many drug makers. The bioavailability radar plots of the tested phytochemicals indicated that the phytochemicals were fairly inside the pink area, indicating their drug-likelihood with a better bioavailability profile [37]. Computational methodologies and procedures, which have proven to be more favorable than in vitro and in vivo research, can be used to avert huge financial losses later in the drug development process.…”
Section: Bioavailability Radar and Toxicity Predictionmentioning
confidence: 99%